Pengambangan Bahan Ajar E-Book Sejarah Lokal Awal Masuk dan Berkembangnya Islam di Sumatera Barat - Agustin, Vanny Noer; Aisiah, Aisiah (Jurnal Kronologi, 2024)
This research was motivated by the difficulty of history teachers finding local history teaching materials, especially about the entry and development of Islam in Minangkabau. The research objectives are; 1) identify the steps for developing local history E-Book teaching materials on the beginning of the entry and development of Islam in Minangkabau, and 2) analyze the feasibility of local history E-Book teaching materials on the beginning of the entry and development of Islam in Minangkabau. This research is research and development (Research and Development R&D). The development model uses a 4D model (Define, Design, Development, Disseminate). The trial subjects for E-Book teaching materials involved history experts (lecturers at the FIS UNP history department) and teaching materials experts (lecturers at the FIS UNP history department). Data were collected using a validation sheet in the form of a 4 category Likert scale. Data analysis uses the average formula. The results of the material feasibility test were shown by an average score of 3.43 (very feasible) by two historical material experts, while the average score of the E-Book teaching material feasibility test was 3.63 (very feasible) by two material experts. Keywords: teaching materials, E-Books, history learning, local history, Islam in Minangkabau.